2015
DOI: 10.1038/srep09447
|View full text |Cite
|
Sign up to set email alerts
|

The extent of inflammatory infiltration in primary cancer tissues is associated with lymphomagenesis in immunodeficient mice

Abstract: Xenotransplantation of human cancers into immunodeficient mice is a very useful approach for studying human tumor biology. However, the occasional occurrence of lymphomagenesis in some mice can spoil the model and must be investigated in detail. We found that a high percentage (32.5%, 26/80) of cancer patient-derived xenografts (PDXs) resembled lymphoma in NOD/SCID mice. Of the 26 xenografts, 23 were human-derived expressing human CD45 (hCD45+) and proved to be of the B-cell subtype (CD3-/CD20+), and they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 20 publications
1
52
1
1
Order By: Relevance
“…In this study, 2 out of 9 PDXs showed morphological characteristics of lymphoma (22.2%). Although the number of the reports on the lymphomagenesis in PDXs are still limited, other two reports present that the incidence of lymphomagenesis in the PDX transplanted with human CRC tissues was 3.3% (1/30) and 28.6% (2/7) [8, 9], suggesting that it is important to consider a possibilities of the lymphomagenesis when establishing PDX using the patient CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, 2 out of 9 PDXs showed morphological characteristics of lymphoma (22.2%). Although the number of the reports on the lymphomagenesis in PDXs are still limited, other two reports present that the incidence of lymphomagenesis in the PDX transplanted with human CRC tissues was 3.3% (1/30) and 28.6% (2/7) [8, 9], suggesting that it is important to consider a possibilities of the lymphomagenesis when establishing PDX using the patient CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the frequency of lymphomagenesis is up to 80% in the prostate cancer PDX which will be attributed to the low tumorigenicity of the androgen-sensitive prostate cancer [10]. Zhang et al suggested that cancer type, preoperative chemotherapy and inflammation in patient primary cancer were associated with high risk of lymphomagenesis in PDX [8]. They suggested that gastric cancer specimens are more likely form DLBCL PDX than CRC ones, because of chronic mucosal inflammation caused by Helicobacter pylori.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In PDX models with transferred peripheral blood mononuclear cells from the same patient, combination therapy with anti-hCD137 and anti-hPD1 antibodies (urelumab and nivolumab, respectively) significantly slowed tumor growth 115 . Although these data are promising, practical challenges remain to improving use of PDX models in cancer research, including delay between murine engraftment time and patient treatment schedule, lymphomagenesis of human tumors in mice, and cost 16, 116. In one large breast cancer PDX model study, even within the first murine passage, all models showed moderate drift to dramatic clonal selection during tumor growth 117 …”
Section: Preclinical Models Of Gastric Cancermentioning
confidence: 99%